Pengaruh Pasta Gigi Ekstrak Strawberry (Fragaria x ananassa) dan Pasta Gigi Whitening Terhadap Diskolorasi Akibat Minuman Kopi Robusta - Gita Dwi Jiwanda Sovira; Dedi Sumantri; Fira Nurlaila Auliana (Faculty of Dentistry Universitas Andalas, 2023)
Background: Tooth discoloration is a change in the colour of the teeth that can damage aesthetics and can affect a person’s confidence. Coffee is one of the factors causing extrinsic discoloration. The content of caffeine and tannins in coffee can affect the colour to be more yellow. One of toothpastes that can be used to remove stain is whitening toothpaste. The abrasive power contained in whitening toothpaste affects decrease in thickness of enamel surface. Natural ingredients are needed as an alternative, such as strawberries. Strawberries contain elegatic acid and malic acid which can whiten teeth. Objective: The aim of this study is to determine the effect of strawberry extract toothpaste and whitening toothpaste on discoloration caused by robusta coffee drink. Method: This type of research is true experimental laboratory with pre-test and post-test design. 36 samples of post-extraction premolars according to the inclusion criteria were immersed in coffee for 7 days and the initial colour was measured with colorlfex ez spectrophotometer. Samples were divided into 2 groups, group 1: brushing teeth with strawberry extract toothpaste and group 2: brushing teeth with whitening toothpaste for 3 minutes twice a day for 14 days. Final colour measurement with colorlfex ez spectrophotometer. Results: Data analysis using paired t-test with the results in strawberry extract toothpaste group and whitening toothpaste group showed a significant difference before and after treatment with p=0. Conclusion: There is an effect between strawberry extract toothpaste and whitening toothpaste in brightening teeth that are discolorated due to robusta coffee drink.